MicroRNA miR-191 targets the zinc finger transcription factor Egr-1 and suppresses intimal thickening after carotid injury. (1st June 2016) - Li, Yue; McRobb, Lucinda S.; Khachigian, Levon M.
Abstract: Background/objectives: Early growth response-1 (Egr-1) is an immediate-early gene that is rapidly and transiently induced by stimuli such as injury, hypoxia and shear stress and is implicated in a range of vascular disorders. Once activated it regulates the expression of a range of genes, instigating a healing response involved in cellular dedifferentiation, proliferation and migration. Knowledge of the mechanisms underpinning the control of Egr-1 is incompletely understood. MicroRNAs (miRNAs) are small, non-coding, single-stranded RNAs that post-transcriptionally regulate gene expression by mRNA degradation or translational inhibition. Methods: The effects of a double-stranded mature mimic precursor of microRNA miR-191 were evaluated on Egr-1 and intimal thickening after balloon catheter injury to carotid arteries in rats. Results: miR-191 (pre-191) inhibits intimal thickening compared with the precursor mimic miRNA negative control (pre-CTL) 14 days after carotid artery injury. Egr-1 expression was suppressed by miR-191 compared with the pre-CTL group. Moreover miR-191 reduced Ki67 proliferation marker expression. Conclusions: miR-191 negatively regulates Egr-1 and controls neointima formation after vascular injury.